Development of Ecotourism Scenario Based on Seawater Quality Evaluation - La Harudu; La Ode Nursalam; Nurlansi Nurlansi; Agus Sugiarto; Ahmad Tarmizi Abdul Karim; Fahrudi Ahwan Ikhsan; Andri Estining Sejati; Masri Ridwan; Liyushiana Liyushiana; Feri Fadlin (Jurnal Ilmu Lingkungan, 2024)
There were various activities in the Bungkutoko Island Kali Biru Bathing area by PT. Pelindo Nusantara and community settlements can unwittingly impact the quality of the water environment. This study aimed to determine the quality of seawater in the Kali Biru bathing area and develop a sustainable tourism-based environmental engineering concept. This research method uses surveys and laboratory analysis. Examination of water samples is carried out directly. Seawater analysis is descriptive with quality data from the results of water quality tests in testing laboratories whose feasibility levels were determined based on Indonesia's government rule number 22 of 2012. The results showed that three elements had laboratory test values exceeding the threshold value, namely: nitrite (NO2-N), sulfate (SO4), and iron (Fe), which should not be present, but during the study, there were already values for nitrite (NO2-N) of 0.12, 0.006, and 0.0006, sulfate (SO4) of 2.3, 1.4, and 4.8 and iron (Fe) of 0.0012, 0.0019, and 0.001 while the other six elements starting from pH (degree of acidity), salinity (%), nitrate (NO3-N), oil and grease, arsenic (As), and total coliform were within the regional quality threshold sea tourism. Scenarios for developing tourism activities through ecotourism activities.